2013
DOI: 10.1080/02571862.2013.860491
|View full text |Cite
|
Sign up to set email alerts
|

The effect of canola (Brassica napus) as a biofumigant on soil microbial communities and plant vitality: a pot study

Abstract: Canola (Brassica napus) may be incorporated into soil as a biofumigant for control of pathogens such asSclerotinia sclerotiorum. Yet, the effect of biofumigants on natural microbial communities required to maintain soil functions is still unclear. A pot experiment with sunflowers as the crop plant was conducted to assess the biofumigation effect of canola on the soil microbial community. The study consisted of 32 pots containing four treatments of eight replicates each. Each pot contained one sunflower plant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Alternatively, Fusarium spp. were found to be less responsive to BBF at different sampling time points. ,, The temporal variation may be attributed to the degradation effect of applied organic matter in the soil . Such microbial dynamics could have positive effects on the long-term suppression of plant pathogens.…”
Section: Bbf Alters the Diversity And Composition Of Soil Microbiotamentioning
confidence: 95%
See 3 more Smart Citations
“…Alternatively, Fusarium spp. were found to be less responsive to BBF at different sampling time points. ,, The temporal variation may be attributed to the degradation effect of applied organic matter in the soil . Such microbial dynamics could have positive effects on the long-term suppression of plant pathogens.…”
Section: Bbf Alters the Diversity And Composition Of Soil Microbiotamentioning
confidence: 95%
“…53 It influences the carbon (C) cycling patterns, and storage of C and N. 54,55 In several BBF experiments, BBF had fewer bacteria effects than fungi. 31,36,37,47,48,51 In Hu et al's 36 study, an approximate 85% reduction in the fungal population was reported. In contrast, a decrease in bacterial copy number and enhancement of fungal copy number following mustard BBF have also been documented.…”
Section: ■ Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Examples include the use of mustard meal to control M. chitwoodi in potato and forage turnip (Brassica rapa var. rapa) and canola (B. napus) to control soilborne pathogens, including nematodes (Al-Rehiayani et al 1999;Henderson et al 2009;Potgieter et al 2013). Thousands of VOC produced by plants are already known, representing around 1% of their secondary metabolites (Dudareva et al 2006;Loreto et al 2014).…”
mentioning
confidence: 99%